Biophysical characterization and molecular docking studies of imidazolium based polyelectrolytes-DNA complexes: role of hydrophobicity - Manojkumar, Kasina; Charan, K. T. Prabhu; Sivaramakrishna, Akella; Jha, Prakash C.; Khedkar, Vijay M.; Siva, Ramamoorthy; Jayaraman, Gurunathan; Vijayakrishna, Kari (Biomacromolecules, 2015)
Nonviral gene delivery vectors are acquiring greater attention in the field of gene therapy by replacing the biological viral vectors. DNA-cationic polymer complexes are one of the most promising systems to find application in gene therapy. Hence, a complete insight of their biophysical characterization and binding energy profile is important in understanding the mechanism involved in nonviral gene therapy. In this investigation, the interaction between calf thymus DNA (ctDNA) and imidazolium-based poly(ionic liquids) (PILs) also known as polyelectrolytes with three different alkyl side chains (ethyl, butyl, and hexyl) in physiological conditions using various spectroscopic experiments with constant DNA concentration and varying polyelectrolyte concentrations is reported. UV-visible absorption, fluorescence quenching studies, gel electrophoresis, circular dichroism (CD), and Fourier transform infrared spectroscopy (FTIR) have confirmed the binding of polyelectrolytes with DNA. UV-vis absorption measurements and fluorescence quenching revealed that the binding between DNA and the polyelectrolyte is dominated by electrostatic interactions. Additionally, CD and FTIR results indicated that the DNA retained its B-form with minor perturbation in the phosphate backbone without significant change in the conformation of its base pairs. Preference for alkyl side chains (KPIL-Ethyl Br < KPIL-Butyl Br < KPIL-Hexyl Br) toward efficient binding between the polyelectrolyte and DNA was inferred from the binding and quenching constants calculated from the absorption and emission spectra, respectively. Further, in silico molecular docking studies not only validated the observed binding trend but also provided insight into the binding mode of the polyelectrolyte-DNA complex.

Evaluation of imidazolium-based ionic liquids towards vermicidal activity: in vitro & in silico studies - Charan, K. T. Prabhu; Ranjan, Prabodh; Manojkumar, Kasina; Pothanagandhi, Nellepalli; Jha, Prakash C.; Khedkar, Vijay M.; Sivaramakrishna, Akella; Vijayakrishna, Kari (RSC Advances, 2015)
A series of six different ionic liquids (ILs) of the kind 1-alkyl-3-methylimidazolium bromide/hydroxide (IL-Br and IL-OH) tailored with different N-alkyl side chains (ethyl, butyl, octyl) were synthesized and evaluated for their vermicidal activity against the Indian earthworm, Pheretima posthuma. The percentage of paralysis and mortality of earthworms against ILs were recorded in a dose dependent (at different concentrations 2, 4, 8 and 16 mM) and time dependent manner. The ILs with hydroxide as the counter anion (IL-OH) showed higher vermicidal activity compared to their bromide counterparts (IL-Br). Moreover, the ILs with the longest alkyl chain (octyl) were observed to have significant vermicidal activity compared to the rest (ethyl and butyl) as well as the standard drug, Albendazole. Furthermore, theoretical modeling was carried out to visualize the preferential docking positions of these ILs into the active site of beta-tubulin. Fascinatingly, it was found that the ILs with longest alkyl side chain showed remarkable vermicidal activity compared to the rest, and the molecular docking studies not only validated the experimental results, but also showed per-residue interaction analysis between the ILs and the different components of beta-tubulin.

Synthesis, structure and DNA interaction studies of bisphosphoramides: theoretical and experimental insights - Goud, E. Veerashekhar; Sivaramakrishna, Akella; Vijayakrishna, Kari; Rao, C. V. S. Brahmmananda; Khedkar, Vijay M.; Jha, Prakash C. (Inorganica Chimica Acta, 2017)
New bisphosphoramides (having phenyl (EDAPOPh(2)) and ethoxy (EDADEP) substituents attached to phosphoryl groups bridged with ethylenediamine spacer) are synthesized and structurally characterized by spectroscopic techniques as well as elemental analysis. The molecular structure of EDAPOPh(2) was determined by single crystal X-ray diffraction technique. The interaction of these bisphosphoramides with calf thymus DNA (ct-DNA) is investigated using UV-Visible absorption and fluorescence spectral data as well as the DFT calculations. These studies reveal that EDAPOPh(2) and EDADEP interact with DNA in a partial intercalation mode. The intrinsic binding constants K-b of two different bisphosphoramides with ct-DNA were determined by fluorescence spectroscopy as 2.08 x 10(4) and 3.86 x 10(4) M-1 respectively. The results indicated that the two compounds bind to ct-DNA with different binding affinities, i.e. EDAPOPh(2) > EDADEP. The binding mechanism of these bisphosphoramides to ct-DNA is also discussed. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Bisphosphoramides; crystal structure; DNA interaction; Molecular docking